2000
DOI: 10.1161/01.hyp.35.6.1183
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and the Heart

Abstract: Abstract-The active end product of the renin-angiotensin system, angiotensin II (Ang II), through the activation of specific Ang II receptors, regulates cardiac contractility, cell coupling, and impulse propagation and is involved in cardiac remodeling, growth, and apoptosis. We review these subjects, as well as the second messengers that are involved, and the synthesis of Ang II in the heart under normal and pathological conditions. Finally, we discuss the possibility that there is an intracrine renin-angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(82 citation statements)
references
References 111 publications
(150 reference statements)
0
81
0
1
Order By: Relevance
“…Additionally, ACE inhibitors attenuate not only the production of Ang II at a systemic and tissue level, but they also allow the accumulation of bradykinin because they inhibit its degradation [20,21,22,23]. Animal studies have shown that the inhibition of bradykinin degradation contributes more to the reduction in blood pressure than the inhibition of Ang II formation by ACE inhibitors [24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ACE inhibitors attenuate not only the production of Ang II at a systemic and tissue level, but they also allow the accumulation of bradykinin because they inhibit its degradation [20,21,22,23]. Animal studies have shown that the inhibition of bradykinin degradation contributes more to the reduction in blood pressure than the inhibition of Ang II formation by ACE inhibitors [24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that at least in some species, the heart is a site of extrarenal renin production. Other authors have suggested that, whereas renin is not synthesized in the heart under physiological conditions, renin gene expression may be turned on in pathophysiological situations (147). It is interesting to note in this context that an additional truncated renin mRNA has been described in heart tissue which lacks the prefragment of preprorenin and results in the formation of a truncated prorenin protein termed exon 1A renin (103,541).…”
Section: Reninmentioning
confidence: 95%
“…In turn, the terminal two amino acids of angiotensin I are cleaved by angiotensin-converting enzyme (ACE) to yield Ang II, the effector molecule of the renin-angiotensin system (RAS). The presence of a local, as distinct from a systemic RAS, has been established in several organs including the heart, adrenal gland, thymus and ovary [7, 8, 9, 10, 11, 12]. This is also true for the eye, following the identification of RAS components including angiotensinogen, renin and ACE within the eyes of humans, rats and other mammals [13, 14, 15, 16].…”
Section: The Ocular Renin-angiotensin System: Characterization and Nomentioning
confidence: 99%